Assessment knowledge and life-style practices of patients with hypertension among their disease in rural area of Kirkuk city - Abid S. Kumait (Kirkuk Journal of Science, 2015)
Background: hypertension also known as increase of blood pressure is consider a main factor for heart and vascular disease around world . More than 60 % around world suffering from hypertension and lead to dead more than nine million patients per year. Aim of the study:- In order to assess patients knowledge and life-style practices for hypertensive patients in rural area of Kirkuk city , find out the relationship between patients knowledge and some socio-demographic characteristic ( age and gender ). Methodology A descriptive study of a quantitative design was conducted at Alhwija General Hospital in Alhawija district for hypertension patients in Kirkuk city from 3rd July 2013 to the 20th of March 2014. A non-probability (purposive) sample of (200) definitely diagnosed hypertension patients selected from adult patients who were attended to Alhwija General Hospital . For the purpose of data collection, a questionnaire format was constructed which contains (57 ) Demographic data include ( 6 ) items , medical data include (6) items knowledge of the Patients include (36) items and life-style practices for hypertensive patients include (9) items. Statistical analysis was used of 3- likert scale option was used in the rating scale as: (3) for yes , (2 ) for uncertain ,and ( 1 ) for no. Content validity was determined by presenting the questionnaire to a panel of (10) experts. The data were collected through the interviewing . They were analyzed through the application of descriptive statistical analysis (frequency and percentage) and inferential statistical data analysis (chi-square) , T. test and ANOVAs . Results :-The findings of the study indicated that No (62%) of the patients were in age group between (45_64)years , No(74%) were females, No(73%) married ,(73% ) were house wife, (55%) illiterate, (53%) had middle monthly income, also the study show most of the sample were not cigarette smokers that represent (86%),and family history for Hypertension and represent (57.5% ) Conclusions:- The study concluded 70% of the patients have inadequate knowledge related to disease, and 65% of them have inadequate practice regarding to the hypertension control . Also the study concluded that there is a highly significant relationship between hypertension patient’s age and their knowledge. Recommendation :-Based on the results , the study recommended Educational programs should be designed to increase people knowledge , awareness about their life style .Booklet should be prepared and presented to the patients to advise them to leave high amount salt intake, encourage patients about exercise which is considered one of the contributing factors for hypertension and construct a specialized modern centers for dealing hypertensive patients